Application of Learning Model Mind Mapping and Think Pair Share to Improving Activity and Student Learning Results - Wijayanti, Peni Dwi (Classroom Action Research Journal (CARJO), 2017)
Based on interviews and early observations before the research is known that the model by teachers is less varied, student less active in learning activities so that the problems caused to low learning outcomes. Researchers suggest to use more varied learnings models such as mind mapping and think, pair, share (TPS). Because the models can able to fix problems in the classroom. This research uses classroom action research (PK) with qualitative descriptive approach applied in class XI IPS 5 Brawijaya Smart School Malang City. The instrument used is an observation sheet interviews, tests, field notes, and documentation. The results showed student learning activity from cycle I is 68% increase in cycle II is 75%. While the average of the results of learning cycle I after the activity into 74 increased in cycle II to 84. Percentage completed classical learning in cycle I is 61% to 86% in cycle II.Â Keywords: Mind Mapping, Think Pair Share, Learning Activity, Results of Learning